Design of an RME-Based Fractions Textbook in the Luwu Tourism Context to Stimulate Students’ Reasoning Skills - Ikram, Muhammad; Marufi, Marufi; Canne, Suriani (ETDC: Indonesian Journal of Research and Educational Review, 2024)
Students in primary school must think mathematically. However, classroom research shows that students' fraction reasoning is low and teachers' instructional materials don't permit higher-order thinking. This highlights the need for a more relevant and meaningful textbook that matches students' learning patterns. Therefore, this study develops and tests a fractions textbook based on Realistic Mathematics Education (RME) using Luwu tourism to improve primary students' reasoning skills. Two teaching experiment cycles were used for R&D. A total of 23 fifth graders and one teacher from Primary School 5 Tarabbi Indah participated in the study. Expert validation sheets, reasoning rubrics, examinations, and instructor/student questionnaires were used. Research included needs analysis, textbook design, expert validation, first-cycle field testing, product change, second-cycle field testing, and retrospective analysis. Data were descriptively investigated using validation, reasoning, user responses, and cycle comparisons. The findings indicated that the textbook was highly legitimate in content, construct, language, and contextual alignment, according to experts. The first cycle teacher gave 3.8, and the second gave 3.9, while students gave 3.63 and 3.44 in the “practical” category. The textbook worked, as sufficient and very competent reasoning skills increased from 47.8% in the first cycle to 69.6% in the second. Understanding information, evaluating tactics, and presenting mathematical arguments improved. The textbook modifications made these improvements possible by simplifying directions, illustrations, and key subjects. This work improves contextual RME-based teaching materials conceptually and practically. The textbook can assist primary school teachers and schools in planning meaningful, relevant fraction instruction that promotes higher-order thinking.